The development of diabetes complications in GP-centered Healthcare - Karimova, Kateryna; Uhlmann, Lorenz (The American journal of managed care, 2018)
Objectives: To compare the development of diabetes complications, measured in terms of clinical end points, of patients enrolled in general practitioner (GP)-centered healthcare (Hausarztzentrierte Versorgung [HZV]) and patients in usual GP care (non-HZV) over 4 years. Study Design: Retrospective closed cohort study based on German claims data. Methods: The main end points in our evaluation were dialysis, blindness, amputation, stroke, myocardial infarction, cardiovascular disease, hypoglycemia, and mortality. We used Cox proportional hazards regression models for multivariable analysis. Results: We included 217,964 patients in our study: 119,355 were enrolled in HZV and 98,609 were in non-HZV. Compared with non-HZV, the HZV group had a 15.6% lower risk of requiring dialysis during the 4 years of observation. Risks were also lower in the HZV group for all other end points except mortality. Conclusions: The results of the present study indicate that GP-centered healthcare is associated with a delay in the occurrence of serious diabetes complications and reduces the risk of diabetes complications. This may be because GP-centered care is associated with improved coordination of care.